Production pipeline fundamentals for film and game - Dunlop, Renee, ....- (New York : Focal Press, 2014)
Every production is built on the backbone of the pipeline. While a functional and flexible pipeline can't assure a successful project, a weak pipeline can guarantee its demise. A solid pipeline produces a superior product in less time and with happier artists who can remain creative throughout the grueling production schedule. Walk through the foundational layers of the production pipeline, including IT infrastructure, software development practices and deployment policies, asset management, shot management, and rendering management. Production Pipeline Fundamentals for Film and Games will teach you how to direct limited resources to the right technological initiatives, getting the most for every dollar spent.
Includes index.
Keywords: Computer games -- Programming; Video recordings -- Production and direction; Motion pictures -- Production and direction; Project management